Practical assessment and treatment of the patient with headaches in the emergency department and urgent care clinic - Marcus, Dawn A.; Bain, Philip A.; SpringerLink (Online service). (New York Springer, 2011)
Migraine is an extremely common condition affecting 28 million Americans. Fully 1 in every 6 adult women suffers from this malady. Patients with migraine are frequently seen in the Emergency Room and Urgent Care Clinic for acute treatment of their headaches. Headache generally accounts for nearly 3 per cent of all ER visits, resulting in almost 3.5 million visits annually. There currently are no widely used guidelines for the treatment of patients with headache in the ER or UCC, and reducing the number of CT scans remains a key goal for administrators in many ER or urgent care settings. In one.
Electronic reproduction.
Keywords: Headache -- Treatment; Headache -- Diagnosis; Emergency medical services; Electronic books